Perbandingan metode pengajaran tradisional dan modern dalam pembelajaran Bahasa Inggris - Agustina, Rika (Maliki Interdisciplinary Journal, 2025)
English language learning at UIN Maulana Malik Ibrahim Malang utilizes two main methods: traditional (Grammar Translation Method) and modern methods (Communicative Language Teaching/CLT, Task-Based Language Teaching/TBLT). The traditional method focuses on grammar mastery but tends to make students passive. In contrast, modern methods improve speaking and listening skills through active interaction. Observations show that students taught with modern methods are more engaged and motivated. While traditional methods provide a solid grammar foundation, modern methods are more effective in enhancing communication skills. Challenges in modern method implementation include the lack of teacher training.